2019
DOI: 10.1177/0003489419826134
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Model of Tracheal Replacement With Electrospun Nanofiber Scaffolds

Abstract: Objectives: The clinical experience with tissue-engineered tracheal grafts (TETGs) has been fraught with graft stenosis and delayed epithelialization. A mouse model of orthotopic replacement that recapitulates the clinical findings would facilitate the study of the cellular and molecular mechanisms underlying graft stenosis. Methods: Electrospun nanofiber tracheal scaffolds were created using nonresorbable (polyethylene terephthalate + polyurethane) and co-electrospun resorbable (polylactide-co-caprolactone/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 28 publications
(42 reference statements)
1
32
1
Order By: Relevance
“…1 TETGs that are supraphysiologic in compression tests compared to native in vivo models may confer higher rates of graft stenosis; non-resorbable grafts may also contribute to more frequent stenosis (Table 1). 10,11…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 TETGs that are supraphysiologic in compression tests compared to native in vivo models may confer higher rates of graft stenosis; non-resorbable grafts may also contribute to more frequent stenosis (Table 1). 10,11…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen studies were isolated pertaining to the application of electrospun nanofibers as tissue engineered tracheal grafts (TETG) for reconstruction of long segment tracheal defects. 1,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Although the specifics of scaffold design and fabrication vary for each study, Clarke and colleagues describe a representative process: First a custom mandrel was created from stainless steel with dimensions matching those obtained from native juvenile sheep tracheas. 16 Once the desired polymer blend was selected, this solution was electrospun using a custom designed apparatus comprised of 20 gauge blunt tip needles and a high voltage direct current (DC) power supply (Figure 3).…”
Section: Tracheal Reconstructionmentioning
confidence: 99%
“…Zhao et al demonstrated graft tensile and compressive strength greater than that of native trachea when using a seeded and subsequently decellularized stent with the scaffold comprised of polyglycolic acid and metal 92 . Dharmadhikari et al compared nonresorbable and resorbable scaffolds and found that both scaffolds held greater tensile strength than native trachea with nonresorbable scaffold being stiffer than resorbable 93 . However, both scaffold types were complicated by stenosis when implanted in mice with resorbable scaffolds demonstrating tracheomalacia and nonresorbable showing tissue overgrowth.…”
Section: Discussionmentioning
confidence: 99%
“…Graft patency was assessed in vivo with the Trifoil eXplore Locus RS 80 micro-computed tomography (microCT). 6 Live animal scanning was performed on post-operative day (POD) 0; animals were positioned prone following induction of inhalational anesthesia (1%−3% isoflurane in room air at 1–3 L/min). Terminal scans were performed at humane and experimental endpoints with similar positioning.…”
Section: Methodsmentioning
confidence: 99%
“… 5 Allograft outcomes have been limited due to graft immunogenicity and synthetic tracheal scaffolds have exhibited poor epithelialization and neovascularization. 6 , 7 Initially, decellularization was geared toward removal of all native cellular material, thus limiting immunogenicity while preserving a natural scaffold composed of extracellular matrix (ECM). 8 , 9 Decellularized trachea have exhibited regeneration in pre-clinical models, however their clinical applications have remained limited.…”
Section: Introductionmentioning
confidence: 99%